2023
DOI: 10.2196/42346
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing e-Cigarette–Related Videos on TikTok: Observational Study

Abstract: Background As a popular social networking platform for sharing short videos, TikTok has been widely used for sharing e-cigarettes or vaping-related videos, especially among the youth. Objective This study aims to characterize e-cigarette or vaping-related videos and their user engagement on TikTok through descriptive analysis. Methods From TikTok, a total of 417 short videos, posted between October 4, 2018, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Provaping messages are dominant on social media [ 49 - 51 ]. One study demonstrated that while the FDA’s sponsored antivaping hashtag “TheRealCost” only appeared 50 times a month on Instagram, provaping hashtags such as “e-juice” or “e-liquid” appeared more than 1000 times [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Provaping messages are dominant on social media [ 49 - 51 ]. One study demonstrated that while the FDA’s sponsored antivaping hashtag “TheRealCost” only appeared 50 times a month on Instagram, provaping hashtags such as “e-juice” or “e-liquid” appeared more than 1000 times [ 52 ].…”
Section: Discussionmentioning
confidence: 99%